Studi Ekologi Serangga Berpotensi Hama pada Tanaman Jambu Biji (Psidium guajava L.) di Desa Tanjung Anom Kecamatan Pancur Batu, Deli Serdang - Umi Diana Citra; Puji Prastowo (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Pest attacks are one of the main challenges in the management of guava plantations that can hinder plant productivity. This study aims to determine the diversity, dominance, distribution pattern, and association of insects with potential pests in guava plants (Psidium guajava L.) in Tanjung Anom Village, Pancur Batu District, Deli Serdang Regency. The research was carried out from June to August 2025. The selection of tree samples was carried out by purposive sampling, insect observation using the census method, and insect collection using the hand sorting and yellow sticky trap method which was carried out four times. The results of the study found 2,848 insect individuals from 10 species, 8 families, and 3 orders. The value of the diversity index (H') was 1.67 in the medium category, while the dominance index (C) was 0.22 in the low category. The distribution pattern of insects includes clustered distribution (5 species, namely Bemisia tabaci, Aphis gossypii, Ferrisia virgata, Planococcus sp., and Metisa sp.), uniform (4 species, namely Strepsicrates sp., Bactrocera dorsalis, Bothrogonia sp., and Empoasca sp.), and random (1 species, namely Siphanta sp.). Associations showed that there were 47% of very high associations (Oi = 1) and 4% of very low associations (Oi = 0) indicating no association.